A new Middle Jurassic lagoon margin assemblage of theropod and sauropod dinosaur trackways from the Isle of Skye, Scotland - Tone Blakesley; Paige E. dePolo; Thomas J. Wade; Dugald A. Ross; Stephen L. Brusatte (PLoS ONE, 2025)
Although globally scarce, Middle Jurassic dinosaur tracks are known from the Isle of Skye, Scotland, and help indicate the palaeoenvironmental preferences and behaviour of major dinosaur clades. Here, we report an extensive new tracksite from Skye: 131 in-situ dinosaur tracks at Prince Charles’s Point on the Trotternish Peninsula. The tracks occur in multiple horizons of rippled sandstones of the Late Bathonian aged Kilmaluag Formation, part of the Great Estuarine Group, which formed in a locally, shallowly submerged lagoon margin. We assign these tracks to two morphotypes, further divided into four morphotype subgroups, most likely representing large megalosaurid theropods, and sauropods that are either non-neosauropods or basal neosauropods. The trackways, although relatively short, evidence time-averaged milling behaviour, as observed at other tracksites in the Great Estuarine Group. The presence of sequential manus and pes sauropod tracks amends their previous identification by geologists as fish resting burrows, raising the potential that other such structures locally and globally may in fact be dinosaur tracks, and emphasises the predominant occurrence of sauropods in lagoonal palaeoenvironments in the Great Estuarine Group. At Prince Charles’s Point, however, unlike previously described lagoonal assemblages, large theropod trackmakers are more abundant than sauropods.